On a second invasive frog (Anura: Leptodactylidae) from San Andrés, Colombian Caribbean islands: Sobre la segunda rana invasora (Anura: Leptodactylidae) de San Andrés, Caribe insular colombiano - Cubillos-Abrahams, María Victoria; Montes-Correa, Andrés Camilo (Anartia, 2021)
Islands are optimal model systems to understand evolutionary processes such as colonization, speciation, and extinction. Their size and distance to the continent are key factors that shape island biodiversity (Zunino & Zullini 2003, Whittaker & Fernández-Palacios 2007). Human have aided the displacement of species to localities that could have otherwise not taken place through natural dispersal across geographical barriers (Ríos & Vargas 2003). Invasive species, particularly in islands, can cause significant ecological changes in the trophic web structure and habitat composition, including severe impacts on native species and ecosystems (Gutiérrez-Bonilla 2006). Invasive species are included among the severe threats that habitats face (i.e., verexploitation of natural resources, urban development, pollution, ecosystem modification, among others; see Russel & Kueffer 2019).